THE INFLUENCES OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, AND QUALITY OF WORK LIFE ON THE JOB SATISFACTION - Zulkarnain, Dedy; Manurung, Antonius Dieben Robinson (Dinasti International Journal of Management Science, 2020)
This research aims to examine and analyze the influences of transformational leadership, organizational citizenship behavior, and quality of work life on the job satisfaction. This research used causal comparative research design with quantitative method. Samples were calculated by the Slovin method and used proportional stratified random sampling. Subjects were 200 manufacturing employees of Polytechnic X. The results of this research show that there is a positive and significant influence of transformational leadership, organizational citizenship behavior, and quality of work life on job satisfaction, both partially or simultaneously. Managerial implications that can be sugestion for Polytechnic X is that management should pay attention the effective transformational leadership especially on individualized consideration dimension, organizational citizenship behaviors especially on cortesy dimension, and quality of working life especially on adequate and fair compensation dimension, to improve employee’s job satisfaction